Effectiveness of Activities 3R (Reuse, Reduce, Recycle) in Improving the Ecoliteracy of Students in Elementary School - Harmawati, Harmawati; DS, Yulistina Nur (International Conference on Elementary Education, 2020)
Action Research class aims to examine activities 3R (Reduce, Reuse, Recycle) students in the learning IPS in class IV SDN Nagasari VI to improve the eco-literacy of students. The research method in use is a class action research consisting of 3 cycles. The data types in this research are quantitative and qualitative data. Data collection techniques using non-test techniques. The study instruments used are observations, field records and documentation. The results showed an increase in the achievement of students skills during the learning process. It is supported by a percentage of data on Cycle 1 which is 62.06% category enough, Cycle 2 is 77.75% good, Cycle 3 is 93.6% very good category. The results of student behavior in Cycle 1 is 53.05% category enough. Cycle 2 is 73.9% good category. While the cycle of 3 is 95.9% category is very good. From the above statement can be concluded that the 3R activities successfully increase the eco-literacy of students at SDN Nagasari VI